Adaptive sliding mode control for a general nonlinear multicompartment lung model with input pressure and rate saturation constraints. (23rd March 2015) - Hou, Saing Paul; Meskin, Nader; Haddad, Wassim M.
Summary: In this article, we develop an output feedback adaptive sliding mode controller for a general multicompartment lung mechanics model with nonlinear resistance and compliance respiratory parameters. Specifically, for a given clinically plausible reference volume pattern, we develop an adaptive sliding mode controller that accounts for input pressure and rate saturation constraints to automatically adjust the applied input pressure by the mechanical ventilator so that the total lung volume tracks the given reference pattern. The pressure due to lung muscle activity is also considered in the controller design. A Lyapunov‐based approach is presented to show convergence of the closed‐loop system, and the proposed control framework is applied to a two‐compartment lung model to show the efficacy of the proposed control method. Copyright © 2015 John Wiley & Sons, Ltd.